Prefabrication 4.0: BIM-aided design of sustainable DIY-oriented houses. (June 2021) - Ostrowska-Wawryniuk, Karolina
In the context of continuous housing shortage, increasing construction standards and rising labour costs, one of the possibilities to address this array of problems is prefabrication directed towards do-it-yourself (DIY) construction methods. This paper presents a prototype tool for aiding the design of DIY-oriented single-family houses with the use of small-element timber prefabrication. The introduced solution uses the potential of BIM technology for adapting a traditionally designed house to the prefabrication requirements and reduction of waste generated in the assembly process. The experimental tool was developed in the Autodesk Revit software. It incorporates custom Dynamo-for-Revit scripts. The experimental tool implemented the user- and technology-specified boundary conditions and converted an input BIM model into a prefabricated alternative. The tool was tested on the design of a two-story single-family house. The results compare the automated optimized panelization with manual approach. The simulation revealed the possibility of the construction waste reduction by at least 50% when comparing to the non-optimized panelization.